THE HISTORY AND EVOLUTION OF PSORIATIC ARTHRITIS - Öz, Burak; Gündüz, İbrahim (My University, 2025)
Psoriatic arthritis (PsA) is a chronic inflammatory disorder characterised by a heterogeneous clinical presentation involving both the skin and joints. Although the coexistence of psoriasis and arthritis has been recognised since antiquity, PsA remained largely unacknowledged as a distinct disease entity until the mid-20th century. Early descriptions in historical literary sources and archaeological findings provided indirect evidence of PsA, but the conceptualisation of the disease evolved significantly in the 19th and 20th centuries. The introduction of classification criteria by Moll and Wright in 1973 and subsequent developments such as the CASPAR criteria in 2006 established a framework for diagnosis and research. Advances in the understanding of PsA pathogenesis, particularly the discovery of the tumor necrosis factor-? and interleukin (IL)-23/IL-17 pathways, paved the way for biologic therapies and treat-to-target strategies, which have dramatically improved clinical outcomes. This narrative review summarises the key historical milestones and therapeutic breakthroughs that have shaped modern PsA management.
Keywords: Historical review; Psoriatic arthritis; evolution of classification criteria; history of therapeutic approaches